The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12905-019-0876-1
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on reasons for early removal of Implanon among users in Arba Minch town, Gamo Goffa zone, South Ethiopia: a phenomenological approach

Abstract: BackgroundImplanon is one of the cost - effective long acting reversible contraceptive methods used for spacing and limiting births in Ethiopia. Despite the scaling up initiative undertaken by the Ethiopian Government, Implanon uptake is very low compared to short acting contraceptive methods. There is low utilization of Implanon with high level of discontinuation in Ethiopia. Therefore, this study was conducted to explore the reasons for early removal of Implanon among users in Arba Minch town, South Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 19 publications
12
20
0
Order By: Relevance
“…This study identi ed side effects as the main reason for the early removal of LAFP which is consistent with other studies [8,10,[16][17][18][19][20][21][22]. The most frequently mentioned side effects were heavy and irregular menses, weight change, and dizziness.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study identi ed side effects as the main reason for the early removal of LAFP which is consistent with other studies [8,10,[16][17][18][19][20][21][22]. The most frequently mentioned side effects were heavy and irregular menses, weight change, and dizziness.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that most of the participants had information about family planning methods which is consistent with a similar research conducted in Arba Minch town [6]. However, the ndings of demographic and health surveys of Ethiopia showed that women in reproductive age know lesser information on family planning methods [11,12].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations